2020
DOI: 10.1108/jpbafm-02-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up rather than top-down: evidence from Middle Eastern and North African educational institutions

Abstract: PurposeEducational institutions in the Middle East and North Africa (MENA) are striving for better resource management and finance. The bottom-up budgeting approach plays an important role in motivating executives' performance. The main aim of this paper is to discover whether there is a significant difference between bottom-up and a top-down approaches to budgeting in terms of managers' performance.Design/methodology/approachQuestionnaires were distributed to 453 university executives in 21 MENA educational i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…More recently, this trend has also expanded into the East, the Middle East and Africa (e.g. Harun et al , 2020; Komutputipong and Keerasuntonpong, 2019; Upping and Oliver, 2012; Mah'd, 2020; Mkasiwa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, this trend has also expanded into the East, the Middle East and Africa (e.g. Harun et al , 2020; Komutputipong and Keerasuntonpong, 2019; Upping and Oliver, 2012; Mah'd, 2020; Mkasiwa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies including Myint, et al, (2019); Sugioko, (2010); Leach-López, et al, (2009); Adler & Reid (2008); Yuen (2007); found positive correlation between budgetary participation and job performance. Previous studies reveal that this method of budget participation improves budget adequacy, satisfaction, trust, and performance in workplace environment (Mah'd, 2020;Sugioko, 2010;. According to recent studies like Mah'd's (2020), there is a significant performance difference between a top-down and bottom-up approach.…”
Section: Role Of Budget Participation On Job Performancementioning
confidence: 98%